2007
DOI: 10.1590/s1020-49892007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment and socioeconomic factors: a population-based survey of an urban locality in southern Brazil

Abstract: Objective. To provide the first population-based data on deafness and hearing impairment (OR = 12.55;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
74
1
38

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 7 publications
19
74
1
38
Order By: Relevance
“…This datum differs from some classic -as well as present -studies on presbycusis which show that men present earlier HL -in addition to higher levels -than women 4,5,23,40 . Other authors, however had already proved there is no such relation 24 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This datum differs from some classic -as well as present -studies on presbycusis which show that men present earlier HL -in addition to higher levels -than women 4,5,23,40 . Other authors, however had already proved there is no such relation 24 .…”
Section: Discussioncontrasting
confidence: 99%
“…This result not only confirms previous studies but also what was expected by the researchers, since it has been described in both national and international literature 5,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The age of the individuals caused an increase in auditory thresholds, which may lead to an even more harmed speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Four studies considered the mean of three frequencies (i.e. 500Hz, 1Khz and 2Khz) and established the mild hearing loss from 26dB 15,16,18,24 . The studies using the cutoff point for mild hearing loss from 26dB showed greater variability in the prevalence of hearing loss: 7.1 to 23.8%…”
Section: Resultsmentioning
confidence: 99%
“…2 In this study, 2,427 children more than four year olds were evaluated. The population was composed of 1,040 systematically chosen households in 40 randomly selected census tracts (dwelling clusters).…”
Section: Introductionmentioning
confidence: 99%